Water recycling method in wastewater treatment of water-jet loom
Through the combined use of Fe3O4/Cu/AC catalyst and flocculant, the Fenton reaction is promoted to generate reactive oxygen species, which solves the problem of low water utilization in wastewater treatment of water jet loom, and achieves effective degradation and conductivity of COD and SS The reduction in wastewater treatment has improved the efficiency and economicality.
Patent Information
- Application Number
- CN202411460894.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-27
AI Technical Summary
The water utilization rate in wastewater treatment of water jet looms is low, and it is difficult for the prior art to effectively remove COD, SS and oil, which affects the hardness and conductivity of the reused water.
The water jet loom wastewater is treated with Fe3O4/Cu/AC catalyst, flocculant and coagulant. The Fenton reaction is stimulated through visible light irradiation to generate reactive oxygen. Combined with flocculation and sodium ion exchange processes, the magnetic carrier is separated and recovered, and the conductivity is reduced. Rate.
It improves the utilization rate of wastewater, reduces COD and SS content, reduces the dosage and treatment costs of drugs, simplifies the steps, and achieves effective control of water quality indicators.
Smart Images

Figure BDA0005091836230000091
Abstract
Description
Technical Field
[0001] The invention belongs to the field of wastewater treatment, and in particular relates to a method for recycling water in water jet loom wastewater treatment. Background Art
[0002] Water jet looms have become the most widely used weaving equipment in my country due to their high output, good quality and low weaving cost. However, the weaving production process produces a large amount of wastewater. The wastewater from water jet looms contains a large amount of chemical oxygen demand (COD), ammonia nitrogen (NH3-N) and suspended solids (SS), which can easily cause water pollution. In addition, water jet looms consume a lot of water and have high water quality requirements, making the deep treatment and recycling of water jet loom wastewater an urgent problem to be solved.
[0003] The main technologies for wastewater reuse in the textile industry are: (1) Water jet loom wastewater - flotation - filtration - reuse. This technology is a combination of physical and chemical technologies, mainly for the removal of grease and some chemical slurries, but it is difficult to control the hardness and conductivity of the reused water. (2) Water jet loom wastewater - dosing precipitation - filtration - reuse. It has a good effect on the removal of suspended matter and colloids, but it is also difficult to control the hardness and conductivity of the reused water. In particular, the removal of oil in the wastewater is not thorough, which affects the quality of the reused water. (3) Textile wastewater - biological treatment - precipitation - filtration - reuse. This technology is a typical combination of biochemical treatment. The quality of biological treatment directly affects the quality of the reused water. Not only is it difficult to remove oil, but the conductivity and hardness of the water quality indicators are also difficult to control.
[0004] The patent application with publication number CN101265001 A discloses a method for treating and reusing wastewater from a water jet loom, which includes the following process: (1) the regulated wastewater is lifted to a reaction tank for coagulation + flotation treatment, the separated sludge enters a sludge concentration tank, and the remaining part enters a biological tank for treatment; (2) after biological treatment and sedimentation, the wastewater enters a horizontal flow sedimentation tank together with supplementary source water, in which the wastewater is added with drugs, pH is adjusted, coagulated, and precipitated, and the effluent enters a clean water tank for disinfection; (3) the effluent after disinfection is filtered and then subjected to sodium ion exchange; (4) the treated process water is sent to each water jet loom in the workshop. The invention pre-treats the wastewater from the water jet loom by adopting a grid-coagulation-flotation process. However, due to the use of coagulants, the conductivity of the flotation effluent increases significantly, from 150μs / cm to about 1500μs / cm, which undoubtedly increases the pressure on the subsequent ion removal stage. Summary of the invention
[0005] The purpose of the present invention is to provide a method for recycling water from water jet loom wastewater treatment, thereby solving the problem of low utilization rate of wastewater from water jet loom.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for recycling water from water jet loom wastewater treatment, comprising the following steps:
[0008] S1: Add Fe3O4 / Cu / AC catalyst, flocculant and coagulant aid into water jet loom wastewater; then add H2O2 into the water jet loom wastewater, stir and react for 3-5h under visible light irradiation, adjust the pH of the wastewater to neutral, continue stirring, and separate the generated flocs from the wastewater; the magnetic carrier in the flocs is recycled after magnetic separation.
[0009] S2: The wastewater treated by S1 is filtered and then exchanged with sodium ions; after treatment, it is directed to the water jet loom for use.
[0010] Furthermore, the H2O2 concentration is 25-35%; the wastewater COD is 300-400 mg / L, and the SS is 100-150 mg / L.
[0011] Furthermore, the flocculant is one of polyferric sulfate and polyaluminium sulfate; the coagulant aid is one of cationic polyacrylamide and anionic polyacrylamide.
[0012] Furthermore, the dosage ratio of the catalyst, H2O2, flocculant, coagulant aid and wastewater is 100-150mg:80-100mL:100-150mg:30-50mg:1L.
[0013] Furthermore, the concentration of the regenerated liquid in the sodium ion exchange process is 5-6%, and the regenerated salt solution and cleaning water are separated from the waste water for treatment.
[0014] Furthermore, the catalyst is prepared by the following steps:
[0015] Activated carbon (AC), FeCl3·6H2O, FeCl2·4H2O and CuCl2·2H2O were dissolved in deionized water, and stirred continuously for 1-2 hours. Then, a 5 mol / L NaOH solution was added dropwise at a constant dripping rate. Then, the pH was adjusted to 10.0-11.0, and stirring was continued for 2-3 hours. After sealing and standing for 10-12 hours, the mixture was filtered and dried at 105-110°C to obtain a Fe3O4 / Cu / AC precursor.
[0016] Under nitrogen protection, Fe3O4 / Cu / AC was heated to 500-520°C at a heating rate of 10-11°C / min, calcined at a constant temperature for 2-2.5 hours, cooled and cleaned, and dried at 55-60°C for 10-12 hours to obtain Fe3O4 / Cu / AC catalyst.
[0017] Furthermore, the particle size of the activated carbon is 180-220 meshes; and the dripping rate of the 5 mol / L NaOH solution is 10-12 mL / min.
[0018] Furthermore, the usage ratio of the activated carbon, FeCl3·6H2O, FeCl2·4H2O, CuCl2·2H2O, and NaOH solution is 6-7g: 3.5-4g: 1.3-1.8g: 3.5-4.5g: 55-60mL.
[0019] According to Fe 3+ / Fe 2+ , Cu 2+ / Cu and Cu 2+ / Cu + The standard redox potential of Fe is shown in (1) to (3). 3+ More conducive to Cu or Cu + Reduction, Fe 2+ It can be converted from Cu and Cu by simple metal replacement reaction. + Regeneration, as shown in (4) and (5):
[0020] Fe 3+ +e→Fe 2+ E0=0.77V (1)
[0021] Cu 2+ +2e→Cu E0=0.34V (2)
[0022] Cu 2+ +e→Cu + E0=0.17V (3)
[0023] ≡Fe 3+ +≡Cu→≡Fe 2+ +≡Cu 2+ (4)
[0024] ≡Fe 3+ +≡Cu + →≡Fe 2+ +≡Cu 2+ (5)
[0025] Due to the irradiation of visible light (hv), the Fe3O4 / Cu / AC catalyst absorbs visible light and due to the Fe 3+ Photoreduction to Fe 2+ and Cu 2+ Photoreduction to Cu + And more ·OH is produced, as shown in (6) and (7):
[0026] ≡Fe 3+ +OH- +hv→≡Fe 2+ + OH (6)
[0027] ≡Cu 2+ +OH - +hv→≡Cu + + OH (7)
[0028] Beneficial effects of the present invention:
[0029] (1) The Fe3O4 / Cu / AC catalyst used in the present invention can undergo Fenton / Fenton-like reactions. 2+ It can cause H2O2 to decompose and generate OH, and H2O2 can then bind Fe 3+ Reduction to Fe 2+ OOH is generated, Fe is generated 2+ It may further react with H2O2 to generate ·OH. The active ·OH released by the self-decomposition of H2O2 can oxidize the surface-bound Cu to Cu + , and Fe 2+ Similar, Cu + It can also catalyze the decomposition of H2O2 to generate OH and Cu 2+ , the generated Cu 2+ Reacts with H2O2 to generate OOH and Cu + .
[0030] Moreover, Cu or Cu + It can also promote Fe 3+ Reduction to Fe 2+ , play a synergistic role, visible light (hv) irradiation can Fe 3+ Photoreduction to Fe 2+ and Cu 2+ Photoreduction to Cu + This produces more OH, which oxidizes organic matter into CO2, H2O and other by-products.
[0031] (2) The Fe3O4 / Cu / AC catalyst used in the present invention is a heterogeneous catalyst, which broadens the reactive pH range. After adding the flocculant, the Fenton reaction can react without adjusting the pH, thereby reducing the corrosion of the equipment caused by the acidic conditions required by the traditional homogeneous catalyst, saving the amount of reagents required for adjusting the pH, and simplifying the wastewater treatment steps.
[0032] (3) The Fe3O4 / Cu / AC catalyst used in the present invention has good adsorption capacity. AC combined with Fe3O4 makes the material magnetic, which solves the disadvantage that AC is not easy to separate and recycle after use, and makes the catalyst easy to recycle and reuse; at the same time, the addition of the catalyst increases the suspended particles in the water, the number of colloid collisions increases, and the chance of forming flocs increases; the catalyst adsorbs a part of the flocculants, reduces the amount of flocculants used, reduces the conductivity of the wastewater, and reduces the treatment cost. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] This embodiment provides a method for recycling water from water jet loom wastewater treatment, comprising the following steps:
[0036] S1: 6 g 180 mesh activated carbon (AC), 3.9 g FeCl3·6H2O, 1.4 g FeCl2·4H2O and 3.6 g CuCl2·2H2O were dissolved in deionized water, and stirred continuously for 1-2 h. Then, 55 mL 5 mol / L NaOH solution was added dropwise at a constant drip rate. Then, the pH was adjusted to 10.0, and stirring was continued for 3 h. After sealing and standing for 12 h, the mixture was filtered and dried at 105 °C to obtain Fe3O4 / Cu / AC precursor.
[0037] Under nitrogen protection, Fe3O4 / Cu / AC was heated to 500°C at a heating rate of 10°C / min, calcined at a constant temperature for 2.5 hours, cooled and cleaned, and dried at 60°C for 12 hours to obtain Fe3O4 / Cu / AC catalyst.
[0038] S2: Add 100 mg of Fe3O4 / Cu / AC catalyst, 100 mg of polyferric sulfate and 30 mg of cationic polyacrylamide to the wastewater of the water jet loom; then add 80 mL of 30% H2O2 to 1 L of the wastewater, stir and react for 3 hours under visible light irradiation, adjust the pH of the wastewater to neutral, continue stirring, and separate the generated flocs from the wastewater; the magnetic carrier in the flocs is recycled after magnetic separation.
[0039] S3: The wastewater treated by S2 is filtered and then exchanged with sodium ions. The concentration of the regenerated liquid in the sodium ion exchange process is 5%. It is cleaned for 1 hour after regeneration. The regenerated salt solution and cleaning water enter the wastewater and enter the wastewater treatment together with the wastewater. The reclaimed water softened by sodium ion exchange enters the refrigerator for treatment and then is used in the water jet loom.
[0040] Example 2
[0041] The difference between this embodiment and embodiment 1 is that the particle size of the activated carbon in S1 is changed to 220 mesh.
[0042] The remaining raw materials and preparation process remain the same as in Example 1.
[0043] Example 3
[0044] The present embodiment is different from the embodiment 1 in that "3.6 g CuCl2·2H2O" in S1 is replaced with "4.5 g CuCl2·2H2O".
[0045] The remaining raw materials and preparation process remain the same as in Example 1.
[0046] Example 4
[0047] The present embodiment differs from the embodiment 1 in that the "30% H2O2" in S2 is replaced with "35% H2O2".
[0048] The remaining raw materials and preparation process remain the same as in Example 1.
[0049] Example 5
[0050] The present embodiment is different from the embodiment 1 in that "100 mg of polyferric sulfate" in S2 is replaced with "100 mg of polyaluminum sulfate".
[0051] The remaining raw materials and preparation process remain the same as in Example 1.
[0052] Example 6
[0053] The present embodiment is different from the embodiment 1 in that "100 mg polyferric sulfate" in S2 is replaced with "150 mg polyferric sulfate".
[0054] The remaining raw materials and preparation process remain the same as in Example 1.
[0055] Example 7
[0056] The present embodiment is different from the embodiment 1 in that the "100 mg Fe3O4 / Cu / AC catalyst" in S2 is replaced with "150 mg Fe3O4 / Cu / AC catalyst".
[0057] The remaining raw materials and preparation process remain the same as in Example 1.
[0058] Comparative Example 1
[0059] S1: 6 g 180 mesh activated carbon (AC), 3.9 g FeCl3·6H2O and 1.4 g FeCl2·4H2O were dissolved in deionized water, and stirred continuously for 1-2 h. Then, 55 mL 5 mol / L NaOH solution was added dropwise at a constant drip rate. Then, the pH was adjusted to 10.0, and stirring was continued for 3 h. After sealing and standing for 12 h, the mixture was filtered and dried at 105 °C to obtain Fe3O4 / AC precursor.
[0060] Under nitrogen protection, Fe3O4 / AC was heated to 500°C at a heating rate of 10°C / min, calcined at a constant temperature for 2.5 hours, cooled and cleaned, and dried at 60°C for 12 hours to obtain Fe3O4 / AC catalyst.
[0061] S2: Add 100 mg of Fe3O4 / AC catalyst, 100 mg of polyferric sulfate and 30 mg of cationic polyacrylamide to the wastewater of the water jet loom; then add 80 mL of 30% H2O2 to 1 L of the wastewater, stir and react for 3 hours under visible light irradiation, adjust the pH of the wastewater to neutral, continue stirring, and separate the generated flocs from the wastewater; the magnetic carrier in the flocs is recycled after magnetic separation.
[0062] S3: The wastewater treated by S2 is filtered and then exchanged with sodium ions. The concentration of the regenerated liquid in the sodium ion exchange process is 5%. It is cleaned for 1 hour after regeneration. The regenerated salt solution and cleaning water enter the wastewater and enter the wastewater treatment together with the wastewater. The reclaimed water softened by sodium ion exchange enters the refrigerator for treatment and then is used in the water jet loom.
[0063] Comparative Example 2
[0064] S1: 3.9 g FeCl3·6H2O, 1.4 g FeCl2·4H2O and 3.6 g CuCl2·2H2O were dissolved in deionized water, and the mixture was stirred for 1 to 2 h. Then, 55 mL of 5 mol / L NaOH solution was added dropwise at a constant rate. The pH was then adjusted to 10.0. The mixture was stirred for 3 h. The mixture was sealed and allowed to stand for 12 h, then filtered and dried at 105 °C to obtain a Fe3O4 / Cu precursor.
[0065] Under nitrogen protection, Fe3O4 / Cu was heated to 500°C at a heating rate of 10°C / min, calcined at a constant temperature for 2.5 hours, cooled and cleaned, and dried at 60°C for 12 hours to obtain Fe3O4 / Cu catalyst.
[0066] S2: Add 100 mg of Fe3O4 / Cu catalyst, 100 mg of polyferric sulfate and 30 mg of cationic polyacrylamide to the wastewater of the water jet loom; then add 80 mL of 30% H2O2 to 1 L of the wastewater, stir and react for 3 hours under visible light irradiation, adjust the pH of the wastewater to neutral, continue stirring, and separate the generated flocs from the wastewater; the magnetic carrier in the flocs is recycled after magnetic separation.
[0067] S3: The wastewater treated by S2 is filtered and then exchanged with sodium ions. The concentration of the regenerated liquid in the sodium ion exchange process is 5%. It is cleaned for 1 hour after regeneration. The regenerated salt solution and cleaning water enter the wastewater and enter the wastewater treatment together with the wastewater. The reclaimed water softened by sodium ion exchange enters the refrigerator for treatment and then is used in the water jet loom.
[0068] Comparative Example 3
[0069] S1: 6 g 180 mesh activated carbon (AC) and 3.6 g CuCl2·2H2O were dissolved in deionized water, stirred continuously for 1-2 h, and then 55 mL 5 mol / L NaOH solution was added dropwise at a constant drip rate. The pH was then adjusted to 10.0, and stirring was continued for 3 h. The mixture was sealed and allowed to stand for 12 h, then filtered and dried at 105 °C to obtain a Cu / AC precursor.
[0070] Under nitrogen protection, the Cu / AC was heated to 500°C at a heating rate of 10°C / min, calcined at a constant temperature for 2.5 hours, cooled and cleaned, and dried at 60°C for 12 hours to obtain a Cu / AC catalyst.
[0071] S2: Add 100 mg of Cu / AC catalyst, 100 mg of polyferric sulfate and 30 mg of cationic polyacrylamide to the wastewater of the water jet loom; then add 80 mL of 30% H2O2 to 1 L of the wastewater, stir and react for 3 hours under visible light irradiation, adjust the pH of the wastewater to neutral, continue stirring, and separate the generated flocs from the wastewater; the magnetic carrier in the flocs is recycled after magnetic separation.
[0072] S3: The wastewater treated by S2 is filtered and then exchanged with sodium ions. The concentration of the regenerated liquid in the sodium ion exchange process is 5%. It is cleaned for 1 hour after regeneration. The regenerated salt solution and cleaning water enter the wastewater and enter the wastewater treatment together with the wastewater. The reclaimed water softened by sodium ion exchange enters the refrigerator for treatment and then is used in the water jet loom.
[0073] Comparative Example 4
[0074] S1: Add 100 mg Fe3O4, 100 mg polyferric sulfate and 30 mg cationic polyacrylamide to the wastewater of water jet loom; then add 80 mL H2O2 with a concentration of 30% to 1 L of wastewater, stir and react for 3 hours under visible light irradiation, adjust the pH of the wastewater to neutral, continue stirring, and separate the generated flocs from the wastewater; the magnetic carrier in the flocs is recycled after magnetic separation.
[0075] S2: The wastewater treated by S1 is filtered and then exchanged with sodium ions. The concentration of the regenerated liquid in the sodium ion exchange process is 5%. It is cleaned for 1 hour after regeneration. The regenerated salt solution and cleaning water enter the wastewater and enter the wastewater treatment together with the wastewater. The reclaimed water softened by sodium ion exchange enters the refrigerator for treatment and then is used in the water jet loom.
[0076] Comparative Example 5
[0077] S1: Add 100 mg FeCl2, 100 mg polyferric sulfate and 30 mg cationic polyacrylamide to the wastewater of water jet loom; then add 80 mL H2O2 with a concentration of 30% to 1 L of wastewater, stir and react for 3 hours under visible light irradiation, adjust the pH of the wastewater to neutral, continue stirring, and separate the generated flocs from the wastewater; the magnetic carrier in the flocs is recycled after magnetic separation.
[0078] S2: The wastewater treated by S1 is filtered and then exchanged with sodium ions. The concentration of the regenerated liquid in the sodium ion exchange process is 5%. It is cleaned for 1 hour after regeneration. The regenerated salt solution and cleaning water enter the wastewater and enter the wastewater treatment together with the wastewater. The reclaimed water softened by sodium ion exchange enters the refrigerator for treatment and then is used in the water jet loom.
[0079] Comparative Example 6
[0080] The difference between this comparative example and Example 1 is that no additional visible light irradiation is performed in S2.
[0081] The remaining raw materials and preparation process remain the same as in Example 1.
[0082] Performance tests were conducted on Examples 1 to 7 and Comparative Examples 1 to 6. The wastewater had a COD of 354 mg / L, a SS of 115 mg / L, and a conductivity of 618 μs / cm.
[0083] According to the "Water and Wastewater Monitoring and Analysis Method" of the State Environmental Protection Administration, the water quality of each embodiment and comparative example of the present application was monitored:
[0084] The results are shown in Table 1:
[0085] Table 1
[0086]
[0087] The degradation rates of Comparative Example 6 and Example 1 were further tested, specifically, the time required for the two catalysts to degrade the COD in the water jet loom wastewater to ≤40 was compared, and the results are shown in Table 2:
[0088] Table 2
[0089] project Time required for wastewater COD≤40mg / L Example 1 90min Comparative Example 6 180min
[0090] As can be seen from Table 1, compared with Example 1, the only difference between Examples 2, 4 and 7 is the amount of raw material added and the changes made by the raw material replacement within a reasonable implementation range, which have little effect on the final result; compared with Example 1, the difference between Example 3 and Example 1 is that the unbalanced ratio of Fe and Cu leads to an imbalance in the synergistic catalytic reaction of Fe and Cu, thereby reducing the catalytic efficiency of the catalyst; compared with Example 1, since the iron ions dissociated from the flocculant polyferric sulfate will participate in the Fenton reaction of the catalyst, the catalytic efficiency of the catalyst is improved, so the COD removal rate is slightly higher; compared with Example 1, the difference between Example 6 and Example 1 is that the amount of flocculant is increased, but at the same time the conductivity in the wastewater is also increased, which is not conducive to subsequent treatment. The catalyst used in the present application reduces the amount of flocculant while achieving the same effect, saving reagents and processing costs.
[0091] Compared with Example 1, the difference between Comparative Example 1 and Example 1 is that the lack of Cu component in the catalyst not only causes the lack of Cu-guided Fenton-like reaction, but also ≡Fe 3+ Cannot be reduced to ≡Fe 2+ , reducing the amount of ·OH produced and the amount of COD oxidized; in Comparative Example 2 compared with Example 1, after removing AC from the catalyst components, on the one hand, the adsorption carriers of Fe and Cu are missing, and the circulation effect of the catalyst is reduced. On the other hand, the lack of adsorption effect of AC requires the addition of more flocculants and coagulants, which increases the conductivity of the wastewater; in Comparative Example 3 compared with Example 1, the lack of Fe phase directly affects the cyclability of the catalyst; in Comparative Example 4 compared with Comparative Example 1, the catalytic efficiency of Fe3O4 alone is lower than that of Fe3O4 / AC, and it has no adsorptive property; in Comparative Example 5 compared with Example 1, although the catalytic efficiency of the homogeneous catalyst FeCl2 is high, the requirement for pH is high, which undoubtedly increases the cost of adjusting the pH of the solution and increases the risk of equipment corrosion, and the homogeneous catalyst is difficult to recover, further increasing the application cost; in Comparative Example 6 compared with Example 1, the results are not much different. In order to explore the effect of light on the reaction system, the degradation rate test is further carried out.
[0092] It can be seen from Table 2 that when the COD content in the spray-woven wastewater is reduced to 40 mg / L, Example 1 only takes 90 min, while Comparative Example 6 takes 180 min, indicating that adding visible light can reduce the COD content in the spray-woven wastewater to 40 mg / L. 3+ Photoreduction to Fe 2+ and Cu 2+ Photoreduction to Cu + , thereby promoting the Fenton / Fenton-like reaction process in the reaction system and degrading organic matter.
[0093] In summary, the water reuse method for treating water jet loom wastewater provided by the present invention can effectively reduce COD and SS in water jet loom wastewater. The prepared catalyst is recyclable, which reduces the cost of using the agent, can improve the utilization rate of water jet loom wastewater, and has good application prospects in the field of wastewater treatment.
[0094] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0095] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for recycling water from water jet loom wastewater treatment, characterized in that: The steps include: S1: Add Fe3O4 / Cu / AC catalyst, flocculant and coagulant aid into the water jet loom wastewater; then add H2O2 into the water jet loom wastewater, stir and react for 3-5h under visible light irradiation, adjust the pH of the wastewater to neutral, continue stirring, and separate the generated flocs from the wastewater; the magnetic carrier in the flocs is recycled after magnetic separation; S2: The wastewater treated by S1 is filtered and then exchanged with sodium ions; after treatment, it is directed to the water jet loom for use.
2. The method for reusing water from water jet loom wastewater treatment according to claim 1, characterized in that: The H2O2 concentration is 25-35%; the wastewater COD is 300-400 mg / L, and the SS is 100-150 mg / L.
3. The method for reusing water from water jet loom wastewater treatment according to claim 1, characterized in that: The flocculant is one of polyferric sulfate and polyaluminium sulfate; the coagulant aid is one of cationic polyacrylamide and anionic polyacrylamide.
4. The method for reusing water from water jet loom wastewater treatment according to claim 1, characterized in that: The dosage ratio of the catalyst, H2O2, flocculant, coagulant aid and wastewater is 100-150mg:80-100mL:100-150mg:30-50mg:1L.
5. The method for reusing water from water jet loom wastewater treatment according to claim 1, characterized in that: The concentration of the regenerated liquid in the sodium ion exchange process is 5-6%, and the regenerated salt solution and cleaning water are separated from the waste water for treatment.
6. The method for reusing water from water jet loom wastewater treatment according to claim 1, characterized in that: The catalyst is prepared by the following steps: AC, FeCl3·6H2O, FeCl2·4H2O and CuCl2·2H2O were dissolved in deionized water, and stirred continuously for 1-2 hours. Then, a 5 mol / L NaOH solution was added dropwise at a constant dripping rate. Then, the pH was adjusted to 10.0-11.0, and stirring was continued for 2-3 hours. The mixture was sealed and allowed to stand for 10-12 hours, and then filtered and dried at 105-110°C to obtain a Fe3O4 / Cu / AC precursor. Under nitrogen protection, Fe3O4 / Cu / AC was heated to 500-520°C at a heating rate of 10-11°C / min, calcined at a constant temperature for 2-2.5 hours, cooled and cleaned, and dried at 55-60°C for 10-12 hours to obtain Fe3O4 / Cu / AC catalyst.
7. The method for recycling water from water jet loom wastewater treatment according to claim 6, characterized in that: The particle size of the AC is 180-220 meshes; the dripping rate of the 5 mol / L NaOH solution is 10-12 mL / min.
8. The method for recycling water from water jet loom wastewater treatment according to claim 6, characterized in that: The usage ratio of AC, FeCl3·6H2O, FeCl2·4H2O, CuCl2·2H2O and NaOH solution is 6-7g:3.5-4g:1.3-1.8g:3.5-4.5g:55-60mL.
Citation Information
Patent Citations
Method for processing wastewater by adsorbent combined with magnetic disc separation technology and application thereof
CN102399042A
Method for treating and recycling water-jet loom wastewater
CN105236666A
Method for integrated treatment of dyeing wastewater by using magnetic activated carbon
CN105439238A
Nanometer Cu-Fe3O4@peanut shell carbon composite material as well as preparation method and application thereof
CN112473668A
Composite coagulant for landfill leachate treatment and preparation method thereof
CN118637726A
